171 SEX AND PHYSICAL EXERCISE: ONE SIZE DOES NOT FIT ALL. (15th December 2022) - Lodi, Elisa; Modena, Maria Grazia; Donati, Federica; Rodighiero, Eleonora; Reggianini, Letizia; Lodi, Giovanni
Abstract: Differences in regulation and adaptations in response to exercise between men and women Numerous cardiovascular adjustments occur during exercise so that cardiac output (CO) rises linearly as a function of VO2 to meet the increased demands of muscular work. There are several genetic, anatomical and hormone sex-related differences that impact the hemodynamic and structural cardiovascular response to exercise. From a hemodynamic point of view, women have lower CO. Females have lower Stroke Volume (SV) and smaller increase in SV in response to exercise, mainly due to their smaller cardiac size/mass, so the main mechanism to enhance CO in women is the increase of HR. Maximum HR has been shown to be similar between females and males and depends mainly on the age rather than on gender. Furthermore, women have lower maximal oxygen uptake (VO2max) values, mainly due to their lower CO, together with differences in peak Da-vO2. Blood volume, hemoglobin, and hematocrit values are 15– 20% lower in women, and sex-based differences exist in pulmonary structure and respiratory function, resulting in a lower oxygen supply for the same quantity of blood flow than men. Moreover, females have lower systolic and diastolic peak blood pressures as compared to males, as they experience a greater drop in systemic vascular resistance during exercise and have lower CO. This could be the reason of the higher occurrence of post-exercise hypotension in women. From a structural point of view, regular physical training induces cardiac remodeling and structural adaptations to improve SV reserve. Trained women exhibited smaller left ventricular wall thickness, cavity size and mass compared to age and fitness-matched men. Women were reported to maintain a normal left ventricular geometry, with a relatively larger increase of cavity dimensions compared with men, evidently influenced by the type of sport praticated. These sex-related differences in cardiac adaptations may be partially explained by the higher concentrations of endogenous anabolic hormones in males and higher hypertrophic potential of male cardiac tissue compared to women. Heart size accounts for many of the sex-based differences in cardiac functional and structural responses, however, it may not entirely account for sex-related cardiovascular differences as they tend to shrink when parameters are normalized for body surface area and lean body mass, suggesting that other factors, such as different body composition, may play a role and indexed parameters should be analyzed rather than absolute values. The more and more large participation of women in a broad variety of sport, together with the increasing awareness about the existence of relevant sex-related differences in response to training, confirm the need to include sex as a biological variable to consider for optimal tailored exercise intervention. Identifying and understanding sex-specific differences is crucial, both from a clinical point of view, as they could impact exercise rehabilitation and prevention strategies, and from a sport and physiological point of view, both in terms of improving performances and reducing injuries.